2010
DOI: 10.1002/pros.21236
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 is a substrate for prostate specific antigen (PSA) in human seminal plasma

Abstract: Background Galectin-3 is a multivalent carbohydrate-binding protein involved in cell adhesion, cell cycle control, immunomodulation, and cancer progression, including prostate cancer. Galectin-3 function is regulated by proteolytic cleavage that destroys galectin-3 multivalency while preserving carbohydrate-binding activity. In human semen, galectin-3 is present in seminal plasma and is also associated with prostasomes, exosome-like vesicles secreted by the prostate. In the current study, we characterized the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…As with human tears, gelatinolytic activity and MMP9 immunoreactivity have been identified in human seminal plasma, however, endogenous metalloproteases purified from seminal plasma have failed to cleave galectin-3. 40 It is now clear that other proteases, such as prostate specific antigen, MMP13, neutrophil elastase, and leishmanolysin, can also degrade galectin-3. 40-43 Exploring whether these or other candidates are responsible for the proteolytic degradation of galectin-3 at the ocular surface could bring novel insights into the mechanisms of epithelial dysfunction in dry eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…As with human tears, gelatinolytic activity and MMP9 immunoreactivity have been identified in human seminal plasma, however, endogenous metalloproteases purified from seminal plasma have failed to cleave galectin-3. 40 It is now clear that other proteases, such as prostate specific antigen, MMP13, neutrophil elastase, and leishmanolysin, can also degrade galectin-3. 40-43 Exploring whether these or other candidates are responsible for the proteolytic degradation of galectin-3 at the ocular surface could bring novel insights into the mechanisms of epithelial dysfunction in dry eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 phosphorylated at serine 6 showed reduced binding to laminin and asialomucin and resulted in a diminished ability of galectin-3 to protect cells from cisplatin-induced apoptosis (1). Glycogen synthase kinase ␤ (GSK-3␤) is responsible for phosphorylation of serine 92 and 96, and these phosphorylations are mediated by Axin (29). In our recent study, we demonstrated that galectin-3 could be phosphorylated by c-Abl at Tyr-79, -107, and -118, where Tyr-107 is the major phosphorylation site (2).…”
Section: Discussionmentioning
confidence: 99%
“…PSA was demonstrated to cleave galectin-3 between Tyr-107 and Gly-108 and produce a functionally active, monovalent lectin (29). Because Tyr-107 is the major phosphorylation site, we checked the ability of active PSA to cleave galectin-3 phosphorylated on Tyr-107.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations